Ball change in tennis: How does it affect match characteristics and rally pace in Grand Slam tournaments? - Carboch, J.; Blau, M.; Sklenarik, M.; Siman, J.; Placha, K. (Journal of Human Sport & Exercise, 2020)
Tennis balls degrade after fast racket and ground impacts until they are changed after agreed number of games. The aim is to analyse the new (after the ball change) and used balls (prior to the ball change) match characteristics and the frequency of rally shots in matches in the Australian Open, French Open and Wimbledon in 2017. Paired samples t-tests and Cohen d were used to compare the point duration, number of rally shots, time between the points, rally pace and work to rest ratio among these tournaments. There was a significant difference in rally shots number played with the new balls (4.17 ± 0.86) compared to the used balls (4.60 ± 1.10) in female matches (p = 0.047); in males matches large effect size was found (d = -0.83) in the same variable with the new balls (4.44 ± 0.57) and used balls (4.95 ± 0.66), both happened in the Australian Open. No difference was found between the new and used balls in the rally pace in all the observed events. The Wimbledon match characteristics were least affected by the ball change. The ball degradation affected the match characteristic the most in the Australian Open, in terms of more rally shots, but not slowing down the rally pace. Our findings inform us how the ball change can affect the game performance in professional tennis.